No paradise yet : the world's women face the new century - Mirsky, Judith; Radlett, Marty; Panos Institute (London: PANOS/Zed, 2000)
Journalists from many countries contributed to this review of the status of women around the globe. They consider social and cultural improvements in the lives of women and the task that remains to provide women with real human rights.
Sexuality under wraps: acknowledging adolescence in India -- Tested to their limit: sexual harassment in schools and education institutions in Kenya -- Sacred knots and unholy deals: the road towards pro-women legal reform in Egypt -- No paradise yet: women and child custody laws in Bangladesh -- A field of her own: women and land rights in Zimbabwe -- Women no cry: female-headed households in the Caribbean -- Legalised cruelty: anti-women laws in Pakistan -- Democracy in the nation, but not at home: domestic violence and women's reproductive health in Chile -- File under "hurt": domestic violence in Sri Lanka -- Less than human treatment: maternity protection in Kenya -- Business orphans: maternity rights and child care in the Philippines -- No mother's day for women workers: sex discrimination in Mexico.
Includes bibliographical references (p. [233]-257).
Keywords: Frau. -- -- swd; Aufsatzsammlung. -- -- swd; Soziale Situation. -- -- swd; Women -- -- Social conditions; Entwicklungsländer.